Intranasal insulin administration decreases cerebral blood flow in cortico‐limbic regions: A neuropharmacological imaging study in normal and overweight males. Issue 1 (22nd October 2020) - Wingrove, Jed O.; O'Daly, Owen; Forbes, Ben; Swedrowska, Magda; Amiel, Stephanie A.; Zelaya, Fernando O.
Abstract: Aim: To assess and compare the effects of 160 IU intranasal insulin (IN‐INS) administration on regional cerebral blood flow (rCBF) in healthy male individuals with normal weight and overweight phenotypes. Methods: Thirty young male participants (mean age 25.9 years) were recruited and stratified into two cohorts based on body mass index: normal weight (18.5‐24.9 kg/m 2 ) and overweight (25.0‐29.9 kg/m 2 ). On separate mornings participants received 160 IU of IN‐INS using an intranasal protocol and intranasal placebo as part of a double‐blind crossover design. Thirty minutes following administration rCBF data were collected using a magnetic resonance imaging method called pseudocontinuous arterial spin labelling. Blood samples were collected to assess insulin sensitivity and changes over time in peripheral glucose, insulin and C‐peptide. Results: Insulin sensitivity did not significantly differ between groups. Compared with placebo, IN‐INS administration reduced rCBF in parts of the hippocampus, insula, putamen, parahippocampal gyrus and fusiform gyrus in the overweight group. No effect was seen in the normal weight group. Insula rCBF was greater in the overweight group versus normal weight only under placebo conditions. Peripheral glucose and insulin levels were not affected by IN‐INS. C‐peptide levels in the normal weight group decreased significantly over time following IN‐INS administration but not placebo. Conclusion: Insulin‐induced changes within key regions of the brain involved in gustation, memory and reward were observed in overweight healthy male individuals. Following placebo administration, differences in gustatory rCBF were observed between overweight and normal weight healthy individuals.